Prevalência do risco de sarcopenia em idosos não institucionalizados e sua associação com internação hospitalar e mortalidade - Machado, Paula Pexe Alves (2022)
Sarcopenia is an aging condition commonly associated with adverse health outcomes. Its occurrence can consequently increase the risk of hospitalization and mortality. The early detection of the risk of sarcopenia suggests intervention and early diagnosis, reducing outcomes such as increased hospital admissions and death. Objective: To assess the prevalence of risk of sarcopenia in community-dwelling elderly and its association, along with other risk factors common to the aging process, with hospitalization and death from any cause. Methods: This is a prospective cohort study, including community-dwelling elderly people in two large cities in the state of Mato Grosso, Brazil. We assessed the risk of sarcopenia in 449 individuals using the SARC-CalF score. All the elderly were followed up and then the risk of sarcopenia was associated or not with hospitalization or death during the 2-year period. Results: The incidence of death and hospitalization was 6% and 8.4%, respectively. By multivariate analysis, smoking was a predictor of death (OR: 3.44; 95% CI: 1.01- 11.69), while multimorbidity (OR: 2.02; 95% CI: 1.20-3, 39) and the risk of sarcopenia were predictors of hospitalization (OR : 1.80; 95% CI: 1.04-3.12). Conclusion: The prevalence of risk of sarcopenia was 24.9% in the elderly studied. Risk of sarcopenia and multimorbidity were the only risk factors independently associated with hospitalization over a two-year period in this population. The only risk factor for mortality was smoking.